Intrinsic Motivation of University Students in Participating in Physical Fitness Training Programs: 大學生參加健身訓練課程的內發動機 - MAK, David; NG IP, Kit Wan Judy (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this study was to examine the intrinsic motivation of University students in pursuing physical fitness training programs. 224 university undergraduate students (81 males and 143 females) who participated voluntarily in fitness training courses were included in this study. Participants were asked to complete a 7-item questionnaire to find out their intrinsic motivation of participating in the fitness training programs. Ratings of the questionnaire range from 1 (strongly disagree) to 5 (strongly agree). The motivation factors were ranked according to their mean scores. It was found that "to keep fit and strong" was top of the list, followed by "to improve health" and "to improve outlook". The implications of the rank order were discussed in the paper. Factor analysis of the motivation factors showed that there were two sub-factor components: physical factor and social factor. The reliability coefficients of the factors were 0.58 and 0.83 respectively. One way ANOVA results showed that significant difference was only found between genders in relation to the social factor. Social factor was seen to be a more important motivating factor in female participants of physical fitness training programs. 本文旨在研究大學生參加健身訓練課程的內發動機。共有二百二十四名大學本科生自願參加這個研究，他們在參加課程後填寫一份有七條題目的問卷。問卷答案幅度由一(強烈反對)至五(強烈贊成)。動機因素方面以平均值去排列等級。結果顯示"保持身體強健"居於首位，跟著的是"改善健康"和"改善外表"。文中亦提及排列等級結果的含意。因子分析結果指出問卷內容有兩個次組合："體質"和"社交"。它們的信度係數分別是0.58和0.83。單向方差分析法表示"性別"和"社交"有顯著差異。"社交"被認為是女性參加健身訓練課程的一個重要內發動機。